The ‘son of God’ in the Gospel of John and its relevance for Muslim–Christian dialogue - Rashid, Ungaran; Harlan, Mark (Springer, 2023)
The term ‘son of God’ has been a source of confusion and controversy in the history of Christian–Muslim encounter. Christian tradition regards the gospel according to John as the account which most clearly portrays the deity of Christ and points to his being the ‘son of God’ as proof of his divinity and equality with God. This chapter presents a Muslim scholar’s challenge to this understanding. After examining the term in the Hebrew scriptures, he argues that the term ‘son of God’ in John’s gospel refers to an anointed king (messiah) who, as heir of the Davidic kingdom, has authority to act as God’s surrogate on the earth. The equality of the son does not refer to a divine nature but his being God’s unique agent possessing full authority from God. It is not a claim to be on par with God or an incarnation of God. A Christian scholar’s response, after explaining the broad scope of usage of ‘God’ and ‘son of God’ in the Jewish scriptures, agrees with the exegetical emphasis on divinity as referring to Jesus’ unique authority as the Christ. Yet there are other nuances of meaning, such as his revelatory relationship to God. He then traces developments from John’s usage to those in later Christian theology. Questions over the inner nature of God in Christian Trinitarian theology and Muslim kalam debates are a related, but different topic, yet one in which there is much common ground. The final section offers implications for Muslim–Christian dialogue that accord with Cornille’s five preconditions.